Spatial technologies to evaluate vectorial samples quality in maps production - Cárdenas Tristán, Abraham; Treviño Garza, Eduardo Javier; Aguirre Calderón, Oscar Alberto; Jiménez Pérez, Javier; González Tagle, Marco Aurelio; Némiga, Xanat Antonio (Universidad Nacional Autónoma de México, 2013)
Despite significant progress in recent years, the methodological conceptualization for assessing quality of vectors that integrate digital mapping is still a complicated task. Due to the fact that there is not an official scheme in Mexico to evaluate vectorial cartographic quality, an alternative methodology is proposed for assessing vectorial quality through analysis of samples at various vectorial scales from the Mexican Republic coverage. The tests conducted with various spatial technologies are under the norm frame TC/211 (ISO19113 e ISO19114), and these have been developed with support of companies who are producers of new spatial technologies and supported by the official producing agency of vectorial information in the country. Of which it is intended searching for appropriate evidences and potential indicators to determine norms or specific models to evaluate quality, for potential benefit of cartographic production in natural resources use and others potential applications of them. The methodology described pursues current advances in research to establish an improvement in the assessment policies in vectorial editing and mapping carried out by international agencies, universities and research centers. To make such a proposal in vectorial assessment quality, recognition was made from different approaches of those who worked in the field.